Personality Types and Technical knowledge Management System: Exploring the Relationship Between Personality and Acceptance of Technical Knowledge Management Systems (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Technical knowledge management systems (TKMSs) are not achieving the usage (acceptance) and the benefits that have been forecasted and are therefore, not enhancing competitive advantage and profits in organizations (Comb, 2004, assessing customer relationship management strategies for creating competitive advantage in electronic business). Hardware and software must therefore identify ways of guaranteeing that all customers accept and use TKMSs. This research studied the relation of personality to technology acceptance of TKMS via the Five-Factor Personality Model (using the Technology Acceptance Model - TAM). This study tested the relationship between major types of personalities and their intention of accepting or refusing to accept TKMSs using an integrative model, which combines the TAM (Davis 1989) with the Five-Factor Model (FFM personality). A survey was conducted to evaluate its personality, its sense and use for the TKMSs by IT, KM, Academia and Psychology LinkedIn Groups, the SIKM Leaders Groups and IEEE. Study results show that TKMS users with the personality characteristic of openness accept the TKMSs more (based on perceived ease of use and perceived usefulness). The results also showed that TKMS users showing the personality trait of extraversion accept the TKMSs better (based on perceived ease of use). It is therefore recommended that organizations and companies investigating and distributing TKMS take into consideration the personalities of users when investigating and designing TKMSs. The potential advantages in the field of information technology could support the competitive benefit and promote the study of relationships with personality aspects in fields of information technology.